Dynamic intertextuality in the Miracula Nynie episcopi: remembering Arator's Historia apostolica. (18th November 2016) - Hillier, Richard
Abstract: It has long been acknowledged that Arator, author of the sixth-century Historia apostolica, was one of the Christian Latin writers with whom the author of the eighth-century Miracula Nynie episcopi was familiar. However, until now the critical consensus has been that the later poem was little more than a 'cut-and-paste' pastiche: Arator's phrases had been chosen largely for their metrical suitability; some were perhaps just 'recycled' borrowings rather than evidence of first-hand reading. But a close comparison of the two texts shows that the extent of the unknown author's borrowings from Arator is far greater than has hitherto been realized. Furthermore it reveals a detailed knowledge of the earlier poem, indeed an intimate understanding of it. This is evident not only in his poetic diction but also in his imitation of specific narrative detail where he displays a tendency to simplify his model, rendering the abstract concrete and the figurative literal.